Implementasi Algoritma Kruskal Dalam Menentukan Rute Terdekat Pada Tempat Pariwisata di Daerah Lombok Tengah - Ni Made Ayu Ulandari; Amrullah Amrullah; Junaidi Junaidi; Sri Subarinah (Pendidikan Matematika FKIP Universitas Mataram, 2021)
When visiting several tourist attractions at once with limited time and an irregular schedule, of course, visitors choose the closest route to be able to visit all the places to be visited at once. This study uses an algorithm, namely the Kruskal algorithm, which aims to find the closest route to visit the five tourist attractions at once in Central Lombok Regency. The tourist attractions in question are Tanjung Aan Beach, Kuta Mandalika Beach, Sukarara Village, Sade Hamlet, Benang Kelambu Waterfall. This type of research is applied research which is generally a type of descriptive research that encourages further research. This study applies a modified Kruskal algorithm so as to produce 4 alternative closest routes with different starting points to be able to visit the five tourist attractions at once in Central Lombok Regency, namely 1) If the journey starts from Tanjung Aan Beach or Benang Kelambu Waterfall, the closest route is 60,1 km; 2) If the journey starts from Kuta Mandalika Beach, the closest route is 73.6 km; 3) If the journey starts from Sade Hamlet, the closest route is 73.6 km; 4) If the journey starts from Sukarara Village, the closest route is 82.9 km